WORKSHOP ON APPLICATION OF ADMINISTRATIVE SERVICES DEWI MOTOR KELAPA DUA JAKARTA - Andi Budi Cahyono; Sahni D. P. Skom. MMSi Sahni D. P. Skom. MMSi (Jurnal Sistem Informasi, 2003)
Writing is about a problem in the application administration services on the goddessof the motor repair shop. The author recommends that this application is made withcomputer to solve a problem in the consumer financial payment, this application isused to enhance the effectiveness and quality of employment in the services to bemore efficient administration.This application is saving the consumer finance payment of administrative data into areport and weekly. The final part of this writing programs attached as supporters ofthe administration application service on motor goddess workshop.